EFEKTIFITAS TEKNIK PENGAJARAN LISTENING SECARA ONLINE - Hasriani G; Rahmad Risan (Universitas Muhammadiyah Ponorogo, 2022)
Teaching English cannot be separated from teaching language skills, including Listening. This study aims to find out the views of students regarding the effectiveness of online learning technique applied by lecturer in teaching listening course. This research is a qualitative descriptive study. Data was collected through a questionnaire. The data collected were analyzed qualitatively by describing the information obtained through a questionnaire. The subjects of this study were 4th semester students of the English Education study program, Faculty of Languages and Literature, Universitas Negeri Makassar who had programmed the Intensive Listening course. The results showed that based on the results of the questionnaire, about 67% of students considered that online listening teaching was quite effective because the methods and materials presented by the lecturers were well received by them so that their listening skills improved. 10% of students think that they have problems in learning listening online because of internet network disturbances and limited internet quota. In addition, there are also difficulties with vocabulary. However, about 10% of students think that teaching listening offline or face-to-face is more effective than teaching listening online. They prefer to interact directly with lecturers. Around 13% of students think that teaching listening both offline and online is the same. It can be concluded that online listening teaching is effective in improving students' knowledge and skills as long as it is supported by methods, materials and devices that are in accordance with learning objectives.